Anaerobic microbiota: spatial-temporal changes in the sediment of a tropical coastal lagoon with ephemeral inlet in the Gulf of Mexico - Torres-Alvarado, María del Rocío (2016)
Sulfate-reducing bacteria (SRB) and methanogenic archaea (MA) share common niches in coastal sediments during the terminal phases of the anaerobic mineralization of organic matter. The purpose of this study was to analyze the spatial - temporal variation of SRB and MA in the sediments of a tropical coastal lagoon with ephemeral inlet (La Mancha, Veracruz, Gulf of Mexico) and its relationship with environmental changes. A total of 24 sediment samples were collected during the dry (April, May), rainy (July, September) and Northern (November, February) seasons in the period 2013-2014. Microbiological analyses included the quantification of the viable SRB and MA with different substrates, as well as mineralization experiments to determine the effect of sulfate on acetate oxidation. The analyzed environmental variables in the sediments included: temperature, pH, Eh, salinity, sulfates, H2S, volatile solids, carbohydrates, and granulometric characteristics. Major changes occurred between the dry and rainy seasons. During the dry season, sulfate-reducing abundance was significantly greater with lactate (8.3x105 - 1.2x107 cells / g) and propionate (1.8x105 - 6.6x106 cells / g) as substrates, while the MA that use methanol were dominant (4.2x105 - 9.1x106 cells / g). In contrast, during the rainy season, hydrogenophylic (2.6x105 - 8.3x106 cells/g) and acetoclastic (5.4x105-6.4x106 cells / g) MA increased significantly and SRB decreased in the analyzed substrates. An apparent competition for acetate was observed, with a greater oxidation in the media with sulfates in the dry season (0.06 mM acetate / g sediment / day), and a greater oxidation in the media without sulfates in the rainy season (0.02 mM acetate / g sediment / day). SRB and MA were present throughout the sediment column, however SRB dominated in the first centimeters of the sediment while MA were abundant in deeper layers. In conclusion, SRB and MA together played a role in the mineralization of organic matter in the sediments of La Mancha lagoon, with sulfate-reduction dominating in the dry season (closed inlet) and methanogenesis during the rainy season (open inlet). Changes in rainfall and river input in this lagoon significantly affect salinity and sulfate content, the main factors that regulate the dynamics of SRB and MA in the sediments.